Harald Høffding and the historical roots of the Bohrian concept of symbol - Pringe, Hernan Bruno (2020)
In this paper we analyze the historical roots of the Bohrian concept of symbol. More precisely, we argue that Bohr takes Kantian elements from Høffding´s philosophy in order to develop his own concept of symbol. For this purpose, firstly, we focus on the two different senses that Bohr gives to the concept of symbol. Then, we study how each of these senses is related to different aspects of Høffding's philosophy and we show the connection between the Bohrian and the Kantian concept of symbol by means of Høffdings mediation.